Petani Perkebunan Kelapa Sawit dalam Perspektif Pengembangan Komunitas - Mudiyono, - (Jurnal Ilmu Sosial dan Ilmu Politik, 2006)
Given the lucrative nature of palm plantation business Indonesian governemt has been highly supportive to its expantion. Nucleus Estates and Smallholders Development Scheme was set out on the name of empowering local farmers. This article reviews the extent community empowerment succesful in achieving that objective.